Gender Differentials in Primary Sexual Abstinence among the Youth in Zambia - , Thankian Kusanthan, Christopher Mapoma (Archives of Current Research International, 2018)
The main aim of the current study was to examine factors affecting primary sexual abstinence among the male and female youth in Zambia. Data employed in this study was derived from the 2013 Zambia Demographic Health Survey. Logistic regression analysis was used to identify influencers of primary sexual abstinence by considering socio-economic variables. Among strong predictors identified were age, religion, wealth status, working status, reading newspapers, watching television and drinking alcohol. Based on the study’s findings, 35 percent of males and 31 percent of females reported practising primary sexual abstinence (PSA). The female youth from rich backgrounds were 1.8 times more likely to report practising primary abstinence compared to those from poor backgrounds. The male youth aged between20-24 were 5 times more likely to practice primary sexual abstinence compared to those aged between 15-19. Drinking alcohol was negatively associated with the likelihood of practising primary sexual abstinence. This study has demonstrated that socio-economic and demographic variables have a significant influence on primary sexual abstinence among the youth. As such, interventions that seek to fight HIV and teen pregnancies through abstinence in Zambia must take into consideration these aspects while paying special attention to the role these factors play on gender.